A glimpse on influences of ginger and its derivatives as a feed additive in finfish farming: A mini-review - Lee Seong Wei; Albaris B. Tahiluddin; Wendy Wee (Heliyon)
Ginger (Zingiber officinale) has emerged as a promising feed additive in aquaculture due to its reported benefits for fish health and growth. Possessing a range of bioactive compounds, ginger exhibits antimicrobial, anti-parasite, immunostimulatory, anti-inflammatory, anti-oxidative, and growth-promoting properties. This review provides a comprehensive overview of recent research on dietary ginger and its derivatives for fish. It explores the various forms, bioactive compounds, biological activities, and preparation methods of these feed additives. The discussion focuses on the impacts of dietary ginger and its derivatives on growth performance, flesh quality, hematology profile, antioxidative responses, immune system, and disease resistance stimulation in fish. Additionally, the review examines the mechanisms of action of these additives and explores the optimal supplementation levels for inclusion in fish diets. Previous studies reported the optimal doses of dietary ginger and its derivatives were ranged from 0.0002 to 4 % of diet whereas 0.0004 % for bathing treatment. Bioactive compounds such as phenolic acids, flavonoids, zingerone, gingerols, shogaols, and paradols were responsible to the ginger and its derivatives beneficial effects. Overall, the findings suggest that dietary ginger and its derivatives hold significant promise for enhancing growth and health in fish farming.